Familization risks, defamilization risks and older women. (4th May 2021) - Chau, Ruby C. M.; Yu, Sam W. K.
ABSTRACT: This article is about the familization and defamilization risks faced by older women. Such risks are generated by the lack of one or both of two conditions: the freedom to choose whether or not to perform certain family roles; and the capacity to maintain a reasonable standard of living. Examples are drawn from findings of a qualitative study in Hong Kong, in which 40 older women aged 65 or above were interviewed to discuss their experiences of issues relating to the risks and their diverse preferences of how these issues should be handled.